Simulation Method of Assessing the Destructive Effect of Fragmentation - Maciej PODCIECHOWSKI (Symulacyjna metoda oceny skuteczności rażenia odłamkowego, 2019)
The paper presents an outline of a simulation method for assessing the fragmentation effectiveness of ammunition equipped with proximity fuses. The method, developed at the Military University of Technology (MUT – Warsaw, Poland) is based on an unambiguous fragmentation action model with a defined and justified degree of simplification. It is a versatile method suitable for all weapons, designed to test the effects of individual parameters describing shells decomposition on the effectiveness of their fragmentation.
Keywords: ocena skuteczności rażenia odłamkowego